Sistem Informasi Kepegawaian pada PT Sumber Medika Persada - Yoko Saputra Dewa; Muhammad Rachmadi (Jurnal Teknologi Sistem Informasi, 2023)
Personnel Information System is a component that interconnected to process and distribute information. The Personnel Information System requires attention so the management of personnel data and information can be archived and organized properly. This research topic is important for PT Sumber Medika Persada because the company does not have a Personnel Information System to coordinate applications, attendance, permits, leave, and the delivery of company internal information yet. This system will be developed using the Rational Unified Process (RUP) methodology which there are 4 stages, namely the beginning to find problems that exist in the company by conducting observations, interviews, and literature studies. Then the planning stage is to analyze the existing problems using PIECES analysis and causal analysis. The next stage is the construction stage to start building the application, and the last stage is the transition where trials are carried out on the applications that have been built. Eventually, the results of this study are expected to help all the problems that exist in PT Sumber Medika Persada so that the company can continue to face the ever-increasing technological developments